The impact of electronic information sources on collection development: a study of current practice at UiTM branches library / Syed Mohammed Alhady Syed Ahmad Alhady ... [et al.] - Syed Ahmad Alhady, Syed Mohammed Alhady; Abdul Rahman, Abd. Latif; Mohamed Ghazali, Asmadi; Hassan, Rosli (2007)
This study sets to look at the impact of electronic information sources on collection development at twelve UiTM branches library. The issues being looked into cover to what extent do the librarians interact with Internet-based technologies and electronic information sources. Areas of study include materials budget, training, and readiness. This study covers twelve UiTM branches library and data gathered through questionnaires and interview. .Results showed that effective training skill and competencies are the most important factors that contribute to readiness and effectiveness of library staff in dealing with electronic information sources. While, material budget allocation does not have any relationship and does not influence the readiness and effectiveness of the library staff.